การศึกษาความน่าจะเป็นในการสร้างผลตอบแทนจากการลงทุนในกองทุนเลียนแบบดัชนีตลาดหลักทรัพย์แห่งประเทศไทย - ทวีวัฒน์ ฆนัทนันท์ (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2018)
A Study of Probability of Return on Investment in SET Index Fund aimed to 1) study the probability of return on Baht Cost Lump-sum (BCL) Investment 2) study the probability of return on Baht Cost Average (BCA) Investment 3) compare the probability of return on investment in SET Index Fund between BCL investment and BCA investment. The study utilized secondary data of net asset value per unit obtained from SCB SET Index Fund over the past 13 years of SCB Asset Management Co. Ltd. The calculation to identify average rate of return was based on 4 periods of investment time of 1, 4, 7, and 10 years. Then the probabilities of return on investment of these 4 periods were calculated. The study results of probability of return on investment in SET Index Fund of BCL investment and BCA investment revealed that, based on investment periods of 7 and 10 years, there were no chances of loss in both types of investment. For BCL type at 7- year and 10- year periods, the probabilities of average rate of return in the range between 10.01 percent up to 15 percent were as high as 0.9103 and 0.5095 with arithmetic means of 12.32 percent per year and 10.00 percent per year respectively. As for BCA type, at 7- year period, the probability of average rate of return over 15 percent was as high as 0.8791 with arithmetic mean of 17.49 percent per year; while at 10- year period, the probability of average rate of return in the range between 10.01 percent up to 15 percent was as high as 0.9185 with arithmetic mean of 11.53 percent per year. Concerning the distribution of average rate of return, the study result indicated that the longer of investment time would lead to the lower of distribution of average rate of return in both types of investment in SET Index Fund. Keywords: Probability, Rate of return, SET Index fund